Exercise physiology for health, fitness, and performance - Plowman, Sharon A.; Smith, Denise L. (Wolters Kluwer, 2017)
The new edition of Plowman and Smith's renowned text continues to the authoritative textbook for teaching Exercise Physiology. This engaging and beautifully designed text integrates theoretical and research based basic exercise physiology with real-world application to prepare students for exciting positions in exercise science, fitness, physical education, athletic training, rehabilitation, coaching and/or allied health professions. Accessible and engaging, the 5th Edition offers coverage of foundational science and critical exercise physiology topics. Organized by independent units (Metabolic, Cardiovascular-respiratory, Neuromuscular-skeletal, and Neuroendocrine-immune) this text offers maximum teaching flexibility for faculty and consistent presentation of material for the student.